BALANCED SCORECARD ANALYSIS AS A TOOL TO MEASURE THE PERFORMANCE OF PROPERTY AND REAL ESTATE COMPANIES LISTED ON THE INDONESIA STOCK EXCHANGE - Maria Tresna Loga; Dyah Shinta Kusumaningtyas; Ade Irawan (Universitas La Tansa Mashiro, 2025)
The purpose of this study is to determine the results of the performance of companies in the property and real estate sectors listed on the Indonesia Stock Exchange (IDX) in the period 2021 – 2024 using the balanced scorecard (BSC) method. The BSC approach assesses four financial perspectives from a financial perspective, a customer perspective, an internal business process perspective and a learning and growth perspective. In this study, Descriptive Quantitative data analysis was used by utilizing secondary data in the form of financial statements from eight (8) companies. The findings of this study reveal that each company shows significant variations in performance in each point of view. PT. Agung Podomoro Land Tbk (APLN) and PT. Summarecon Agung Tbk (SMRA) managed to achieve the highest balanced scorecard, while PT. Lippo Karawaci Tbk (LPKR) and PT. Ciputra Development Tbk (CTRA) faces difficulties in several aspects of performance. This study explains the importance of the application of BSC for comprehensive and strategic performance assessment in increasing the competitiveness of the company